Arterial access-site complications after use of a vascular closure device related to puncture height. Issue 1 (December 2017) - Sartorius, Benjamin; Behnes, Michael; Ünsal, Melike; Hoffmann, Ursula; Lang, Siegfried; Mashayekhi, Kambis; Borggrefe, Martin; Akin, Ibrahim
Abstract Background To analyze differences of access-site complications related to the height of femoral arterial puncture and the use of a vascular closure device (VCD) following percutaneous coronary intervention (PCI). Methods A subgroup of the FERARI study being treated by femoral arterial access and valuable inguinal angiography before implantation of a VCD were included. Inguinal angiographies were systematically reviewed by two independent cardiologists to determine the correct height of femoral arterial puncture. Bleeding complications were documented within 30 days after PCI and were categorized according to BARC, TIMI, GUSTO and FERARI classifications. Results Femoral access point imaging was available in 95 patients compared to 105 patients without. The common femoral artery (CFA) was the most accessed artery in 41%, followed by the femoral arterial bifurcation (39%) and lower access sites distally from the femoral arterial bifurcation (low puncture: 20%). No differences were observed regarding indication of PCI, procedural data and anticoagulation therapies in relation to the heights of femoral arterial access (p  > 0.05). Despite using VCD, arterial puncture at the CFA resulted in numerically highest numbers of overall bleedings (62%) compared to femoral arterial bifurcation (41%) (p  = 0.059). 58% of bleedings occurred after arterial puncture below the femoral bifurcation (low puncture). Though no significant differences of bleedings regarding classifications of BARC, GUSTO, TIMI and FERARI as well as other vascular endpoints were observed regarding puncture height. Conclusions The present analysis demonstrates no significant differences of bleeding complications in relation to the height of femoral arterial puncture and subsequent use of a VCD.